The synthesis of open chain pancratistatin analogues - Thompson, Warren (My University, 2010)
(+)-Pancratistatin is a medicinally useful compound which has been isolated from plants belonging to the Amaryllidaceae plant family. The deceptively simple looking pancratistatin is in fact a complicated molecule; it has six contiguous stereocenters of which four belong to alcohol groups and the other two make up a trans B-C ring junction. In addition, it consists of three fused rings. The medicinal properties and the synthetic challenges set by pancratistatin have attracted the attentions of many synthetic groups. Herein are reported approaches to the synthesis of C-seco pancratistatin analogues. D(-)- tartaric acid was used as the starting material as it contains two of the four stereocenters found in pancratistatin. Organocuprate and rhodium-catalyzed reactions were successfully employed to install one of the two stereocenters required for the trans B-C junction. The rhodium catalysed addition reactions were found to be more efficient: they were easier to set up, the work up was a simple filtration, high conversions and anti-selectivity were observed. The antiselective addition was proved by means of obtaining a crystal structure of 3-((4R,5R)-5- (benzyloxymethyl)-2,2-dimethyl-1,3-dioxolan-4-yl)-3-phenylpropanoic acid - a carboxylic acid derivative of an addition product. Confirmation of the resulting compound, resulting from the attempted ring closure via an isocyanate intermediate - formed through a Curtius rearrangement of an azide - to complete the trans B-C junction has proved, through NMR analysis, to be inconclusive. Unfortunately, this result meant that the synthesis was halted one step away from the formation of a protected open chain pancratistatin analogue. Good progress was made towards the synthesis of open chain pancratistatin analogues and it is said with great optimism that the analogues will eventually be made.